2019
DOI: 10.1080/10872981.2019.1694309
|View full text |Cite
|
Sign up to set email alerts
|

Development of an entrustable professional activities (EPAs) framework for small group facilitators through a participatory design approach

Abstract: Background: Recent reports suggest that faculty development (FD) programs need a structured framework to design training and assess improvement in teaching performance of participants. Entrustable professional activities (EPAs) can serve as a novel framework to plan and conduct structured FD programs, and to assess the proficiency of small group facilitators after training. Objective: The researchers aimed to develop an EPAs framework for small group facilitators. Design: In March 2019, three workshops were or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The central component of ethics teaching is the availability of ethics teachers, the faculty development program must orientate teacher to become better teachers and ethical role model. A participatory research has developed entrustable professional activities for medical teachers (19). There is a total of nine entrustable professional activities and twelve competencies are associated with these professional activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central component of ethics teaching is the availability of ethics teachers, the faculty development program must orientate teacher to become better teachers and ethical role model. A participatory research has developed entrustable professional activities for medical teachers (19). There is a total of nine entrustable professional activities and twelve competencies are associated with these professional activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is a total of nine entrustable professional activities and twelve competencies are associated with these professional activities. There was a hundred percent among participants on professionalism and communication skills competency (19). In a local need assessment survey related to faculty development, it was found that clinical teachers are more interested in in-patient care as compared to the basic science teacher.…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a study in which a framework for structured training of small group facilitators was co-created through student-teacher partnership (Iqbal et al, 2020). We involved students as equal partners in the design process because their voices are usually ignored while designing faculty development programs.…”
Section: Responsible Research Informed By Multiple Perspectivesmentioning
confidence: 99%
“…The gap in teacher evaluation triggers the need for a systematic evaluation system Sommer et al, 2016). Although other teacher evaluation methods, such as video recordings, pre-tests/post-tests, and faculty reports, have been tried in the past, these approaches might not be enough to generate evidence of teaching competence and teacher readiness to perform daily academic tasks proficiently Iqbal, Könings, Al-Eraky, AlSheikh, & van Merrienboer, 2020;. While exploring a potential solution to these challenges, and proposed the utility of entrustable professional activities (EPAs) to design faculty development programs and to evaluate teaching proficiency.…”
Section: Contemporary Challenges In Faculty Developmentmentioning
confidence: 99%
“…This project mainly focused on small group pedagogy while designing EPAs, because it is an increasingly popular pre-clinical teaching and learning instructional strategy in health professional schools worldwide. Small group pedagogy is a student-centered approach that promotes active and collaborative learning, and includes problem-based learning (PBL), teambased learning (TBL), simulation-based learning, and learning through skills lab Iqbal et al, 2020). Despite being frequently used as a teaching and learning approach, facilitating small groups sometimes becomes challenging for the teachers, especially for discipline-based program graduates with limited exposure to small group teaching and learning (Assen, Meijers, Otting, & Poell, 2016;Williams & Paltridge, 2016).…”
Section: Why Focus On Small Group Pedagogy?mentioning
confidence: 99%